LIBIDO AND EJACULATE TRAITS OF PERFORMANCE TESTED BOARS - R. Savić; M. Petrović; D. Radojković; Č. Radović; N. Parunović (Journal of Animal and Plant Sciences, 2014)
The main objective of this study was to score variability of fertility traits of boars as influenced by breed, age at first ejaculation/collection (AFE), the lean meat content (LM), lifetime average daily gain (ADG) and age of boars. The following fertility traits were analysed: libido, duration of ejaculation (DE), ejaculate volume (VOL), the density of the ejaculate (DEN) and sperm motility (MO) of boars. Boars' libido was assessed on the basis of duration of preparing to collection (DPC). The study included 7987 ejaculates from 105 boars of three breeds: Swedish Landrace (SL; n=34), Large White (LW; n=39) and Duroc (n=32). Impact assessment was carried out using the GLM procedure of the statistical package SAS 9.1.3 (SAS Inst. Inc., 2002-2003). Of all the traits analysed, only the DPC and VOL varied under the influence of all investigated impacts. Boars of SL and LW breeds demonstrated superiority in the trait VOL (+12.53 and +11.25 ml) compared to Duroc. Ejaculates of boars with AFE from 23 to 27 weeks had the highest VOL, but with the lowest qualitative properties. Contrary to the negative trend in the manifestation of libido, increase of LM and ADG indicated the trend of increasing DE and VOL. Boars with LM of 61% and higher had the highest VOL, and the differences in relation to the first and second class were +6.32 ml (P<0.01) and +5.18 ml (P<0.05), respectively. The ejaculate volume of the boars with the highest ADG compared to the other classes was higher (P<0.001) by 10.88 and 9.81 ml. Boars in different ADG classes produced ejaculate with differing qualitative property DEN. Correlations between production traits and fertility traits were negligible, and unlike the ADG, only the correlation between LM and DPC was statistically significant (P<0.001).
Keywords: boar; libido; ejaculate traits; lean meat content; average life daily gain